MISSIO DEI AND COMPASSIO DEI: MINORITY CHRISTIANS EXPERIENCING GOD'S ACTS IN THE FACE OF HOSTILITY - Sauer, Christof (Scriptura, 2010)
This article examines what we can learn about being a 'missional church' from reading the book of Acts, with a minority Christian community experiencing God's acts in the face of hostility. Romanian theologian Josef Ton discovers three lessons on suffering and martyrdom in the book of Acts: understanding the sovereignty of God, regarding suffering for Christ as a privilege and honour, and trusting the leading and empowering of the Holy Spirit.